3次元渦巻き型旋回興奮波：スクロールと持続性心房細動 - 山崎, 正俊; 神谷, 香一郎; 本荘, 晴朗; 竹本, 芳雄; カリファ, ジェローム (Transactions of Japanese Society for Medical and Biological Engineering, 2016)
Backgrounds: The mechanisms that maintain persistent atrial fibrillation (PtAF) are incompletely understood. We hypothesized that PtAF were maintained by 3-dimensional (3-D) atrial scroll waves (SWs) anchored in regions of large spatial gradients in wall thickness. Methods and Results: We made optical mapping simultaneously from endocardium and epicardium of the left atrium in Langendorff-perfused PtAF (lasting 21.3±11.9 days, n=8) sheep hearts under increased atrial pressure (12 cmH2O). In PtAF hearts, 3-D SW filaments seemed to span the LA wall from endocardium to epicardium. Numerical simulations using 3-D atrial geometries predicted that, similar to experiments, filaments of meandering atrial SWs stabilized at locations with large spatial gradients in myocardial wall thickness. Furthermore, simulations predicted that ionic remodeling and heterogeneous distribution of stretch-mediated channel conductances contributed to filament stabilization. Conclusions: The heterogeneous wall thickness, stretch together with AF-induced ionic remodeling, are the main factors allowing atrial SW and PtAF maintenance.